The Role of Internal Audit in Fraud Prevention in Bogor Area 1 PT Permodalan Nasional Madani Persero: PERAN AUDIT INTERNAL DALAM PENCEGAHAN FRAUD PADA AREA BOGOR 1 PT PERMODALAN NASIONAL MADANI PERSERO - Aningsih, Erisa Nurfitri (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
Abstract: PT PNM (Permodalan Nasional Madani) Mekaar has 62 branches spread across Indonesia, especially the one the author wants to discuss is PT PNM Bogor Area Bogor 1 branch which has 9 Units with a total of 41,830 customers and a total of 160 employees. With 4 positions as Head of Unit total 9, Deputy Head of Unit total 21, Financial Account Officer total 16, and Account Officer total 112. With the large number of Employees, PT PNM Area Bogor 1 provides Knowledge Sharing through the Operational and Corporate Risk Management Division with the theme "Improving PNM Risk Awareness Culture and Anti Fraud". The author uses the observation method during the training and interviews participants regarding the training on the benefits obtained and suggestions given by the participants. The results of Knowledge Sharing with the theme of Improving PNM Risk Awareness Culture and Anti Fraud are that Employees increasingly understand the definition of Fraud, what types of Fraud are, the risks that arise if Fraud occurs and the impact on themselves if they commit Fraud. This Knowledge Sharing will be held routinely every 6 months to provide an understanding of Fraud and mitigate the occurrence of Fraud. Abstrak:PT PNM (Permodalan Nasional Madani) Mekaar memiliki 62 cabang tersebar di indonesia,khususnya yang mau penulis bahas adalah PT PNM cabang Bogor Area Bogor 1 yang telah memiliki 9 Unit dengan total nasabah 41.830 dan total 160 karyawan . Dengan 4 jabatan yang ada sebagai Kepala Unit total 9, Wakil Kepla Unit total 21, Financial Account Officer total 16, dan Account Officer total 112. Dengan banyaknya jumlah Karyawan  maka PT PNM Area Bogor 1 memberikan Knowlage Sharing melalui divisi Divisi Manajemen Risiko Operasional dan Korporasi dengan tema “Peningkatan Budaya Sadar Resiko PNM dan Anti Fraud”. Penulis melakukan metode observasi selama pelatihan dan melakukan wawancara kepada peserta mengenai pelatihan tentang manfaat yang di dapat dan saran yang diberikan oleh peserta. Hasil Knowlage Sharing dengan tema Peningkatan Budaya Sadar Resiko PNM dan Anti Fraud adalah Karyawan semakin faham tentang definisi Fraud, apa saja jenis Fraud, resiko yang ditimbulkan jika terjadinya Fraud dan dampak pada diri sendiri jika melakukan Fraud. Knowlage Sharing ini akan diadakan rutin setiap 6 bulan sekali untuk memberikan pemahaman akan Fraud dan memitigasi terjadi Fraud.